Water quality prediction using the QUAL2Kw model in a small karstic watershed in Brazil - Camargo, Rodrigo de Arruda; Calijuri, Maria Lúcia; Santiago, Aníbal da Fonseca; Couto, Eduardo de Aguiar de; Silva, Marcos Dornelas Freitas Machado e (Acta Limnologica Brasiliensia, 2010)
The Tancredo Neves International Airport (TNIA) complex is situated in Brazil's Fidalgo watershed. Since its construction, the TNIA complex has attracted urban development, leading to expansion of the complex and occupation of the surrounding area. However, this area lacks basic infrastructure such as wastewater treatment facilities. This paper had the objectives of calibrating and validating a water quality prediction model and of assessing the capacity of small karstic watersheds to assimilate non-point source pollutant loads. We used the QUAL2Kw model for modeling the water quality. We performed model calibration for the rainy period then validated the results for the dry period. The model adequately represented the physical, chemical, and hydraulic aspects of the Fidalgo watershed. The pH, EC, TDS, TP, alkalinity and E. coli presented the closest simulation values for the rainy period. For the dry period, the best simulations were obtained for pH, EC, TDS, TP, and alkalinity. We concluded that the calibration and validation periods had similar RMSE values for flow rate, TDS and DOC. The differences were greater for pH, EC, NO3, TP, and E. coli. The lowest dissolved oxygen contents obtained during the calibration and validation periods were 5.4 and 4.7 mg.L-1, respectively, both of which are higher than the minimum of 4.0 mg.L-1 established by the USEPA for the conservation of aquatic communities, but lower than the minimum of 5.0 mg.L-1established by the Brazilian CONAMA 357. The upper limits for biochemical oxygen demand and total N and P can be met as long as the respective loads increase by no more than 0.361 kg.d-1 O2, 0.022 kg.d-1 N, and 0.010 kg.d-1 P, according to USEPA and 0.361 kg.d-1 O2 and 0.012 kg.d-1 P according to CONAMA 357. The conservation of the water resources in this region should therefore consider the adoption of preventive measures such as protecting exposed soils and decreasing the nutrient influx from agricultural and livestock activities.

O Aeroporto Internacional Tancredo Neves (AITN) está localizado na microbacia do córrego do Fidalgo, Brasil. Desde sua construção, o AITN tem atraído a instalação de indústrias e loteamentos residenciais sem que a região oferecesse condições básicas de infraestrutura. Este trabalho teve por objetivo calibrar e validar modelo de predição da qualidade da água e avaliar a capacidade de assimilação de cargas difusas em microbacia cárstica. Utilizou-se o QUAL2Kw para a modelagem da qualidade da água. A calibração do modelo foi realizada no período chuvoso e a validação para o período seco. O modelo demonstrou ser capaz de representar com habilidade e flexibilidade os aspectos físicos, químicos e hidráulicos observados na microbacia. Os parâmetros pH, CE, STD, PT, alcalinidade e E. coli apresentaram os melhores ajustes entre as previsões do modelo e os dados observados para o período chuvoso. Para o período seco, os melhores ajustes foram obtidos para pH, EC, TDS, TP e alcalinidade. Os valores de REMQ foram similares entre os períodos para vazão, SDT e OD. As maiores diferenças foram observadas para os parâmetros pH, CE, NO3, PT e E. coli. O menor valor de OD obtido na calibração foi de 5,40 mg.L-1 e na validação de 4,70 mg.L-1, valores superiores ao mínimo estabelecido de 4,0 mg.L-1 para conservação das comunidades aquáticas pela USEPA, porém inferior ao limite de 5,0 mg.L-1 estabelecido pela CONAMA 357.Os limites de DBO, NT e PT são atingidos com um acréscimo de carga na microbacia de 0,361 kg.d-1 O2, 0,022 kg.d-1 N,e 0,010 kg.d-1 P de acordo com a USEPA e 0,361 kg.d-1 O2 e 0,012 kg.d-1 P pela CONAMA 357. A conservação dos recursos hídricos dessa região deve ser efetivada com a adoção de medidas preventivas, como a cobertura de solos expostos e a diminuição do influxo de nutrientes de origem agrícola ou pecuária.
Keywords: Water quality; Karstic region; Modeling; QUAL2Kw; Urban pollution; Qualidade da água; Região cárstica; Modelagem; Poluição urbana